Synthesis of manganese-oxide and palladium nanoparticles co-decorated polypyrrole/graphene oxide (MnO2@Pd@PPy/GO) nanocomposites for anti-cancer treatment. Issue 37 (22nd August 2022) - Wu, Jiarui; Wang, Meng; Pan, Yuanjie; Pang, Yipeng; Tang, Yanyan; Song, Chang; Zhu, Jiahui; Zhang, Xian; Huang, Qingli
Abstract : Manganese-oxide and palladium nanoparticle-co-decorated polypyrrole/graphene oxide (MnO2 @Pd@PPy/GO) nanoenzyme composites were synthesized, and could be as a novel "theranostic nanoagent" for cancer treatment due to excellent performance. Abstract : Design and fabrication of novel multifunctional nanomaterials as novel "theranostic nanoagents"with high efficiency and low side effects is important for cancer treatment. Herein, we synthesized manganese-oxide and palladium nanoparticle-co-decorated polypyrrole/graphene oxide (MnO2 @Pd@PPy/GO) nanocomposites, which could be used as a novel "theranostic nanoagent" for cancer treatment. Various spectroscopic and microscopic characterizations of the synthesized MnO2 @Pd@PPy/GO nanocomposites suggest that the nanocomposites are assembled sequentially by graphene oxide, polypyrrole, palladium nanoparticles and manganese-oxide nanoplates. Further research revealed that the nanocomposites had excellent photothermal conversion performance (reached near 50 °C after 10 min of irradiation), pH responsive enzymatic-like catalytic activity and enhanced magnetic resonance imaging (MRI) performance ( r 1 = 7.74 mM −1 s −1 at pH 5.0 and glutathione (GSH)). Cell experiments also testified that combined cancer treatment (the viability of cancer cells is 30%) with photothermal therapy (PTT, the viability of cancer cells is 91% only with irradiation) and chemodynamic therapy (CDT, the viability of cancer cells is 74.7% only with nanocomposites) guided by MRI was achieved when the as-prepared nanocomposites were employed as theranostic nanoagents. This work could provide some new ideas for the controllable synthesis and application of multicomponent nanomaterials.